Corporate Governance and Leverage: Evidence from a Natural Experiment - Stefan Arping; Zacharias Sautner (Tinbergen Institute, 2010)
We argue that the recent corporate governance reform in the Netherlands provides a natural experiment to explore the impact of changes in corporate governance on financing policy. We find that, relative to a control sample of comparable firms outside the Netherlands, Dutch firms significantly reduced their leverage following the passage of the reform. Our findings are consistent with the view that corporate governance improvements reduce the value of debt as a disciplining device.
Keywords: G32; G34; 330; Corporate Governance; Corporate Leverage; Financing Policy; Corporate Governance; Unternehmensfinanzierung; Übernahme; Niederlande; Test